Language Impoliteness in Memes Contesting the 2024 Presidential Election in Indonesia - Anwar, Miftahulkhairah; Amir, Fachrur Razi; Zuhriyah, Siti Aminataz; Purbasari, Rahayu; Rosa, Helvy Tiana (Universitas Pendidikan Mandalika, 2024)
In the context of the 2024 presidential election campaign, the proliferation of memes as a medium of public and supporter expression has become increasingly prominent. Memes serve as a vehicle for political commentary, often reflecting public sentiment and opinion. However, a significant concern arises from the pervasive use of linguistic impoliteness within these memes. This study aims to examine the phenomenon of linguistic impoliteness in memes related to the 2024 presidential election. Employing a descriptive qualitative research method, data were collected from a variety of meme images sourced from the internet. The analysis reveals that linguistic impoliteness in these memes manifests in several forms, including bald on-record impoliteness, positive impoliteness, negative impoliteness, sarcasm, and the withholding of politeness. These forms of impoliteness not only reflect the aggressive nature of political discourse but also have the potential to incite conflict among different political factions. The findings suggest a need for more responsible meme usage, particularly in politically charged contexts, to foster a healthier and more constructive political dialogue. The study concludes that while memes are a powerful tool for political expression, their potential to exacerbate tensions should not be overlooked. Implications for future research include exploring strategies for mitigating the negative impact of impoliteness in online political communication.